Effects of cannabinoid exposure on short-term memory and medial orbitofrontal cortex function and chemistry in adolescent female rhesus macaques - Kohut, Stephen J.; Cao, Lei; Mintzopolous, Dionyssios; Jiang, Shan; Nikas, Spyros P.; Makriyannis, Alexandros; Zou, Chun S.; Jensen, J. Eric; Frederick, Blaise B.; Bergman, Jack; Kangas, Brian D. (Frontiers in Neuroscience, 2022)
Aim There is increasing concern that cannabinoid exposure during adolescence may disturb brain maturation and produce long-term cognitive deficits. However, studies in human subjects have provided limited evidence for such causality. The present study utilized behavioral and neuroimaging endpoints in female non-human primates to examine the effects of acute and chronic exposure during adolescence to the cannabinoid receptor full agonist, AM2389, on cognitive processing and brain function and chemistry. Materials and methods Adolescent female rhesus macaques were trained on a titrating-delay matching-to-sample (TDMTS) touchscreen task that assays working memory. TDMTS performance was assessed before and during chronic exposure to AM2389, following antagonist (rimonabant) administration, and after discontinuation of the chronic regimen. Resting-state fMRI connectivity and magnetic resonance spectroscopy data were acquired prior to drug treatment, during chronic exposure, and following its discontinuation. Voxels were placed in the medial orbitofrontal cortex (mOFC), a region involved in memory processing that undergoes maturation during adolescence. Results TDMTS performance was dose-dependently disrupted by acute AM2389; however, chronic treatment resulted in tolerance to these effects. TDMTS performance also was disrupted by discontinuation of the chronic regimen but surprisingly, not by rimonabant administration during chronic AM2389 treatment. mOFC N-acetylaspartate/creatine ratio decreased after acute and chronic administration but returned to baseline values following discontinuation of chronic treatment. Finally, intra-network functional connectivity (mOFC) increased during the chronic regimen and returned to baseline values following its discontinuation. Conclusion Neural effects of a cannabinergic drug may persist during chronic exposure, notwithstanding the development of tolerance to behavioral effects. However, such effects dissipate upon discontinuation, reflecting the restorative capacity of affected brain processes.